Parosmia and altered taste in patients recovering from Covid 19 - Christine E. Kelly (Clinical Nutrition Open Science, 2023)
Summary: Parosmia is a well-documented consequence of smell loss associated with Covid 19. Those who experience this qualitative olfactory disorder during recovery find that the odour of common foods and household items is distorted, and the experience can range from merely altered to profoundly disgusting. This can lead to a greatly altered relationship with food, including the physical symptoms of loss of appetite, nausea, vomiting, as well as wider reaching issues such as withdrawal from social situations, emotional distancing from others in their close social circles, and anhedonia. There is at present no known cure or intervention to mitigate the condition. The AbScent Parosmia and Phantosmia support group on Facebook became an important resource for patients with this condition during the early part of the pandemic, and the crowd-sourcing of experiences, tips and peer-to-peer advice became a valuable source of information for the community as well as researchers trying to understand the condition. Using protocols described in earlier literature on the use of social media for qualitative research, this paper provides information on the management of parosmia based on the experiences of over 30k patients in the AbScent Parosmia and Phantosmia group on Facebook and 6k member of the AbScent Network.